Impact of smoking cessation counseling among acute myocardial infarction patients on post-hospitalization mortality rates: a systematic review - Alhaijaa Eyad Abu; Alblishi Ismael; Alnaeem Mohammad; Alshraideh Jafar Alasad (Sciendo, 2022)
The current systematic review aimed to assess the impact of smoking cessation counseling (SCC) on patients' short- and long-term mortality after acute myocardial infarction (AMI).